The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1365-2966.2009.16121.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis ofRXTE-PCA Observations of SMC X-1

Abstract: We present timing and spectral analysis of Rossi X‐ray Timing Explorer‐Proportional Counter Array observations of SMC X‐1 between 1996 January and 2003 December. From observations around 1996 August 30 with a time‐span of ∼6 d, we obtain a precise timing solution for the source and resolve the eccentricity as 0.00089(6). We find an orbital decay rate of which is close to the previous results. Using our timing analysis and the previous studies, we construct a ∼30 yr long pulse period history of the source. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
1
15
1
Order By: Relevance
“…We find that a sin i/c, e, and Ω are not well constrained compared to several pointed observations (see, e.g., Raichur & Paul 2010). Moreover, their values are not consistent with each other from different measurements (İnam et al 2010;Raichur & Paul 2010). This could be caused by the variability of the pulse profile (Raichur & Paul 2010).…”
Section: Spin-superorbital Connectioncontrasting
confidence: 79%
See 1 more Smart Citation
“…We find that a sin i/c, e, and Ω are not well constrained compared to several pointed observations (see, e.g., Raichur & Paul 2010). Moreover, their values are not consistent with each other from different measurements (İnam et al 2010;Raichur & Paul 2010). This could be caused by the variability of the pulse profile (Raichur & Paul 2010).…”
Section: Spin-superorbital Connectioncontrasting
confidence: 79%
“…It is interpreted as the reprocessing of X-rays from the accretion disk (Hickox & Vrtilek 2005). Since 1997, SMC X-1 has been well monitored with several X-ray instruments, and the most frequent monitoring was carried out with RXTE between 1996 and 2000 (Henry & Schreier 1977;Inam et al 2010). The full history of the pulse frequency evolution of SMC X-1 up to MJD 52987 (2003 December 14) is reported byİnam et al (2010).…”
Section: Introductionmentioning
confidence: 89%
“…The variation of the n H value may be due to the partial obscuration of the neutron star by the precessing accretion disk or X-ray eclipses. Another possibility for the variation may be an artifact of simple POWERLAW model or the tails of the soft excess components affecting our result (Inam et al 2010). The photoelectric absorption by the interstellar matter is dominated in lower energy range but as we can't go below 3 keV energy due to the limitation of our instrument, its not possible to constraint the n H value precisely.…”
Section: Pulse Profile Hardness Ratio and The Energy Spectramentioning
confidence: 93%
“…All these systems show evidence for alternate spin-up and spin-down phases. In some cases the average spin evolution led to an effective long-term increase or decrease of the NS spin rate (see e.g., Bildsten et al 1997;Inam et al 2010, for more details), and thus the spin periods reported in Table 1 should only be considered as indicative. The spin period of the NS (possibly) hosted in 4U1700-377 is currently unknown.…”
Section: Ten Eclipsing Hmxbsmentioning
confidence: 99%
“…(a) Levine et al (2000), Bildsten et al (1997) but see also Naik & Paul (2004); (b) Bildsten et al (1997), Raichur & Paul (2010b); (c) Rubin et al (1996), Hammerschlag-Hensberge et al (2003); (d) Mukherjee et al (2006), Clark (2000); (e) Inam et al (2010), Raichur & Paul (2010b); ( f ) (a.k.a. IGR J18027-2016) Hill et al (2005); (g) Corbet & Mukai (2002); (h) (a.k.a.…”
Section: Introductionmentioning
confidence: 99%